Edukasi tentang Hak dan Kewajiban Pajak UMKM di Cileungsi Kidul, Kabupaten Bogor - Nurul Aisyah Rachmawati; Rizka Ramayanti (Jurnal Abdimas Berdaya : Jurnal Pembelajaran, Pemberdayaan dan Pengabdian Masyarakat, 2022)
In April 2022, Department of Accounting, Universitas Trilogi Jakarta has organized one of the Tri Dharma Perguruan Tinggi in the form of community service activities. In this case, Department of Accounting, Universitas Trilogi Jakarta held a mentoring class for one of the MSME actors who is a honey producer in Cileungsi Kidul, Bogor Regency. Knowledge about the tax rights and obligations of MSME is still limited. Therefore, it is necessary to provide assistance for the development of MSME, including in the field of taxation. During the COVID-19 pandemic, MSME mentoring classes were carried out virtually. Through this education, it is hoped that MSME actors will be more aware of taxes and have good knowledge about tax rights and obligations. Thus, in the future, MSME will avoid the imposition of tax administration sanctions.